Improving Students' Speaking Ability through Extracurricular Kultum for Student of Madrasah Aliyah - Gama, Muhammad Putra Gama; Ernita Daulay (ENGLISH FRANCA : Academic Journal of English Language and Education, 2024)
Abstract. Activities such as discussions, presentations and daily conversations in English help students hone their speaking skills. Students experience obstacles in learning to speak English where students feel inferior and are afraid of making mistakes when speaking English, which makes them hesitate to participate in conversations. The problem formulation for this research is whether extracurricular activities can improve students' English speaking skills. The aim of the research is to determine the improvement in English speaking skills through extracurricular activities for Madrasah Aliyah Sabilul Mukminin students in Binjai City. This research uses quantitative research methods with an experimental research design. The population is the entire research subject, that is, defined as all members of a well-defined group of people, events, or subjects. The research population consisted of all class XI at Madrasah Aliyah Sabilul Mukminin, Binjai City, consisting of 2 classes totaling 74 students. The sample was determined using a random sample from both classes to select only 1 class as the place for the research experiment. The results of the lottery selected 40 students from class XI-A to be used as a research experimental class with the number. The results of the research showed that the N-Gain price was 0.73 in the high category with a percentage of 73.00% and the calculated results of the significance level of 0.000 were smaller than the significance of 0.05 (0.000<0.05) which means that the change in students' English speaking ability after learning using extracurricular kultum for Madrasah Aliyah Sabilul Mukminin students in Binjai City. The conclusion of the research is that there was an increase in students' English speaking skills after learning using extracurricular kultum for Madrasah Aliyah Sabilul Mukminin students in Binjai City. Keywords: Extracurricular, Culture and Speaking Ability